Ethics in practice an anthology - LaFollette, Hugh 1948- (Malden, MA Wiley/Blackwell, 2014)
A collection of 70 new, revised, and classic essays covering 13 key ethical issues. Through the careful selection of essays, thoughtful organization of the sections, and helpful introductions, this book brings together a collection that integrates ethical theory with the discussion of practical ethical issues.
Pt. I. Ethical theory -- Pt. II. Life and death : Euthanasia ; Abortion ; Animals -- Pt. III. The personal life : Family and sexuality ; Biomedical technologies -- Pt. IV. Liberty and equality : Paternalism and risk ; Sexual and racial discrimination ; Affirmative action -- Pt. V. Justice : Punishment ; Economic justice ; World hunger ; Environment ; War, terrorism, and reconciliation.
Includes bibliographical references.
Keywords: Applied ethics; Ethical problems